2002
DOI: 10.1266/ggs.77.323
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary relationships among rice species with AA genome based on SINE insertion analysis.

Abstract: Previous studies based on morphological and molecular markers indicated that there are two cultivated and five wild rice species within the Oryza genus with the AA genome. In the cultivated rice species, Oryza sativa , a retroposon named p-SINE1 has been identified. Some of the p-SINE1 members characterized previously showed interspecific insertion polymorphisms in the species with the AA genome. In this study, we identified new p-SINE1 members showing interspecific insertion polymorphisms from representative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 41 publications
(58 reference statements)
9
63
1
Order By: Relevance
“…The Pita sequences of O. meridionalis were determined by two independent sequencing experiments. The present findings were inconsistent with a prior phylogenetic tree based not only on sequence variations in Adh1 and Adh2 (Yoshida et al, 2004;Yoshida and Miyashita, 2005), but also on RFLP, RAPD (Ishii et al, 1996;Bautista et al, 2001), and SINE insertion polymorphisms (Cheng et al, 2002), which sug- (Supplementary fig. 2).…”
Section: Polymorphic Sites In the Pita Region Of O Rufipogoncontrasting
confidence: 99%
See 1 more Smart Citation
“…The Pita sequences of O. meridionalis were determined by two independent sequencing experiments. The present findings were inconsistent with a prior phylogenetic tree based not only on sequence variations in Adh1 and Adh2 (Yoshida et al, 2004;Yoshida and Miyashita, 2005), but also on RFLP, RAPD (Ishii et al, 1996;Bautista et al, 2001), and SINE insertion polymorphisms (Cheng et al, 2002), which sug- (Supplementary fig. 2).…”
Section: Polymorphic Sites In the Pita Region Of O Rufipogoncontrasting
confidence: 99%
“…Sequence type B could be corresponding to the H-OB. The H-OB O. rufipogon accessions tested by Huang et al (2008) (Ishii et al, 1996;Bautista et al, 2001;Cheng et al, 2002). Therefore, the direction of the introgression is not clear in our data.…”
Section: Polymorphic Sites In the Pita Region Of O Rufipogonmentioning
confidence: 73%
“…Short interspersed elements (SINEs) of retroposons have also been used for phylogenetic studies, because a single SINE copy, once inserted, remains in the genomic locus. Cheng et al (2002) identified p-SINE1 in the O. sativa genome, and showed that it is a powerful tool for classification of cultivated and wild rice species. Another wild rice accession of O. rufipogon repeatedly used by international teams for QTL studies (IRGC 105491) is originally NIG W0574 collected in 1959 in Malaysia.…”
Section: Contribution Of the Nig Wild Oryza Collection To The Rice Rementioning
confidence: 98%
“…This indicates that the segmental genomic duplication carrying mtRPL27 at S27 occurred before the divergence of the rice AA genome species and that the duplicated segments at S27 spread in each species, except O. glumaepatula, which is the sole South American species possessing the AA genome and is thought to have an African origin (29). Indeed, the O. glumaepatula accessions used in this study were closely related to the O. barthii and O. glaberrima complex (28,30,31) (also see Fig. S6).…”
Section: Resultsmentioning
confidence: 75%